The effect of Polyherbal Unani formulation on melanogenesis mechanism in the treatment of hypopigmentation disorder - Ghali, Shravan Kumar; Rafeeqi, Towseef Amin; Husain, Gulam Mohammed; Javed, Ghazala; Waheed, Mohammed Abdul; Kazmi, Munawwar Husain; Chakraborty, Alokananda (Phytomedicine Plus : International journal of phytotherapy and phytopharmacology, 2022)
•Unani formulas have been used for a very long time to treat a variety of skin issues.•In addition to serving as melanogenic agents, UNIM-004 and UNIM-005 showed a favourable effect on Hypopigmentation Disorder, a factor in vitiligo.•The usage of UNIM-004 and UNIM-005 on B16F10 cells increased parameters such as cell viability, cell morphology, tyrosinase enzyme levels, and cyclic AMP levels. Persons with hypopigmentary disorders are vulnerable to environmental intrusions and cosmetic psychosocial problems. In such circumstances, upregulating melanocytes in terms of proliferation and pigment synthesis is critical. Whereas hypopigmentation disorders can be treated several times, their effectiveness and safety remains unhappy. Due to their outstanding potentials in many treatments, naturally occurring plant extracts are being used widely. In this exploration, we gave one of these a trial. The current study aims to evaluate the impact of herbal Unani formulations which stimulate melanogenesis by modulating-accelerating activity and elucidating the mechanism underlying it. In this study, four Unani formulations, coded as UNIM-001, UNIM-003, UNIM-004, and UNIM-005 were dissolved into three solvents and made into extracts (Aqueous, Hydro-ethanol, and Methanol). The B16F10 cells were treated with different concentrations of UNIM extracts for all experiments such as cell viability, determination of melanin, tyrosinase activity, and cAMP levels. Among these three solvents, the methanolic extract of UNIM-004 and UNIM-005 showed a significant increase in melanin, tyrosinase, and cAMP levels without any cytotoxic effect for 48 h. Whereas UNIM-001 and UNIM-003 have not shown a significant increase in melanin, tyrosinase, and cAMP levels. The above studies indicate that UNIM-004 and UNIM-005 of methanolic extracts increase melanogenesis in B16F10 cells by instigating cAMP levels as well as tyrosinase activity. Current data indicates that these UNIM formulations have the potential for skin darkening which could be used in the therapy of hypopigmentation disorders as a secure melanogenic agent.